Impact of Technology Adoption and Its Utilization on SMEs in Ghana - Selase, Afenya Millicent; Selase, Aphu Elvis; Ayishetu, Abdul-Rahaman; Comfort, Asime Dede; Stanley, Amezado; Ebenezer, Gyan-Acquah (International Journal of Small and Medium Enterprises, 2019)
The study used a quantitative approach to identify technology adoption and its utilization effect on market performance of small and medium enterprises in Ghana, La-Nkwantanang municipality. The study combined the construct Of Technology Acceptance Model and Innovation Diffusion Theory to identify some factors which influence small and medium enterprises to adopt and use internet technology. Furthermore, the study examined some factors which also hinder the adoption and utilization of internet technology among small and medium enterprises. Finally, the study determined the relationship between in internet technology usage among small and medium enterprise and market performance. A sample size taken by the researchers was 100 from the small and medium enterprises in Madina La-Nkwatanang municipality. The researchers used structured questionnaires to gather primary data which was analyzed using smart PLS and SPSS and the following results were obtained perceived ease of use, perceived usefulness of internet technology, compatibility and cost effectiveness are some of the factors that influence the adoption and utilization of internet technology, however, there is a positive relationship between internet technology usage and market performance.